TRADISI NYEPI SUBAK DALAM RANGKAIAN UPACARA BALIK SUMPAH DI DESA GIRI EMAS KECAMATAN SAWAN KABUPATEN BULELENG - Sedana I Made (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Bali is famous as an island that has many unique traditions. The unique tradition found on the island of Bali is generally an ancestral heritage. This tradition contains values that want to be inherited and cannot be changed. The values in the tradition can be a guide in behaving for the supportive community. One of the unique traditions found in Bali is the tradition of the subak nyepi in Giri Emas Village by way of a collective agreement or arrangement in local village customs and traditions with no meaning or traditional ceremony or ritual ceremony. In accordance with the observations made by the authors, the community in Giri Emas Village in the implementation of the Bhuta Yad ceremony had little difference with the people in other regions. Differences of opinion will be the study of the author, but the understanding of the community is more of a priority.Keyword : Subak Nyepi Tradition, Oath Behind Ceremony